2017
DOI: 10.1007/s40261-017-0590-4
|View full text |Cite
|
Sign up to set email alerts
|

Who Receives Nalmefene and How Does It Work in the Real World? A Single-Arm, Phase IV Study of Nalmefene in Alcohol Dependent Outpatients: Baseline and 1-Month Results

Abstract: The data provided by this phase IV study suggest nalmefene is an effective, well-tolerated treatment for alcohol dependence in real-world, clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
5
0
2
Order By: Relevance
“…Se incluyeron 110 pacientes en total de 4 centros de la región española de Cataluña entre 2015 y 2016. Los resultados completos del estudio de fase 4 están disponibles en otra publicación (Barrio, Ortega, Guardia, Roncero, Yuguero y Gual, 2018). La tabla 1 muestras las diferencias entre este estudio y el ensayo de fase 3 de nalmefeno respecto de los variables basales del estudio principal.…”
Section: Resultsunclassified
“…Se incluyeron 110 pacientes en total de 4 centros de la región española de Cataluña entre 2015 y 2016. Los resultados completos del estudio de fase 4 están disponibles en otra publicación (Barrio, Ortega, Guardia, Roncero, Yuguero y Gual, 2018). La tabla 1 muestras las diferencias entre este estudio y el ensayo de fase 3 de nalmefeno respecto de los variables basales del estudio principal.…”
Section: Resultsunclassified
“…A full description of the methods has been described elsewhere [5]. As a summary, this was an observational, multisite, single-arm, phase-IV study, conducted among adult alcohol-dependent outpatients taking nalmefene for the first time.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline and one month results [5] suggested nalmefene was effective in reducing alcohol consumption. They also showed that it was well-tolerated with no serious adverse events, and the satisfaction with the drug of both professionals and patients was high.…”
Section: Introductionmentioning
confidence: 99%
“…Nalmefen wirkt als selektiver Opioidrezeptorligand mit antagonistischer Aktivität am μ- und δ-Rezeptor und mit partieller agonistischer Aktivität am κ-Rezeptor trinkmengenreduzierend bei Alkoholabhängigkeit 18 19 . Ob die Wirkung am κ-Rezeptor (und die mögliche Reduktion anxiogener, anhedoner Symptome) darüber hinaus einen klinisch relevanten Zusatznutzen vermittelt, ist offen.…”
Section: Rückfallprophylaktische Pharmakotherapieunclassified